Analysis of Hydrologic Response to Rain-on-Snow. - Colbeck,Samuel C. (1975)
The equations describing water movement in a dry snow cover are derived and examples of flow through ripe, refrozen and fresh snows are given. The grain size of snow has a large effect on the timing of water discharge. Water is retained by dry snow to raise its temperature and satisfy the irreducible water saturation. These requirements delay and reduce runoff following rain on dry snow.